The Relationship between Early Complementary Feeding and Nutritional Status and Incidence of Diarrhea in Infants Aged 0-6 Months at the 7 Ulu Palembang Community Health Center in 2022 - Fitri Afdhal; Ranida Arsi; Dora Miranti (MultiTech Publisher, 2023)
This study investigates the impact of early complementary feeding on the nutritional status and incidence of diarrhea in infants aged 0-6 months at the 7 Ulu Palembang Community Health Center in August 2022. Employing an observational analytic approach with a cross-sectional design, the study sampled 47 infants using simple random sampling techniques. Data were collected through questionnaires and measurements, and analyzed using Chi-square tests (p < 0.05). The study found a significant relationship between early complementary feeding and poor nutritional status (p = 0.048) as well as the incidence of diarrhea (p = 0.029) in infants. These findings underscore the importance of adhering to recommended feeding guidelines to improve infant health outcomes.